Rapid surface finishing of chemical vapour deposited tungsten carbide hard coatings by electropolishing - Micallef, Christian; Chiu, Cheng-Wei; Zhuk, Yuri; Aria, Adrianus Indrat (Elsevier, 2021)
Tungsten/tungsten carbide (W/WC) coatings deposited through chemical vapour deposition (CVD) exhibit favourable mechanical properties and are widely used to extend the working life and performance of engineering parts which operate in high wear and corrosive environments. Following the coating deposition process, the coated parts must adhere to low surface roughness and geometrical tolerance specifications necessitating the need of a machining or surface finishing operation. Unlike monolithic materials, hard W/WC coatings have low machinability due to their high hardness and superior mechanical properties. In this study, electropolishing, which is independent of the material's hardness and capable of processing parts with complex geometries has been studied as a prospective noncontact machining and surface finishing technique for CVD W/WC coatings. Here we report the electropolishing behaviour of W/WC coatings with an average thickness of 50 ± 15 μm and 1300 ± 50 HV hardness. Optimal electropolishing parameters using 5 wt% sodium hydroxide (NaOH) electrolyte concentration at 21 °C allow a mirror-like surface finish with Ra of less than 50 nm and a change in coating thickness of up to 18 μm to be achieved within 5 min. The change in electrolyte temperature from 21 °C to 40 °C was found to have a significant effect on the electropolishing behaviour due to the formation of a thin and unstable viscous film. The electrolyte concertation of 5 wt% was more stable when compare to 3 wt%, giving an overall better surface finish. EBSD analysis revealed that grains with a {111} orientation were preferentially etched in NaOH.
Keywords: Electropolishing; Tungsten carbide; Chemical vapour deposition; Surface finish